Perbedaan Kadar Kolesterol Serum Darah yang Dibekukan Sebelum Dicentrifuge dan Langsung Dicentrifuge - Henny Eldayanti Mowendu; Putu Ayu Parwati; Ni Ketut Ayu Mirayanti (Pusat Riset dan Inovasi Nasional, 2025)
Errors in the pre-analytical phase are a dominant factor causing inaccurate laboratory test results, including blood serum cholesterol analysis. Pre-examination specimen handling is crucial to ensure the quality of measurement results. This study aimed to compare serum cholesterol levels in blood frozen before centrifugation with those immediately centrifuged. The research method was analytical using a cross-sectional design. A total of 35 respondents were involved, consisting of laboratory staff, emergency room staff, pharmacists, and administration at Sinar Kasih GKST Tentena Hospital. Blood samples were obtained via venipuncture after participants had fasted for 10–12 hours. Each sample was then separated into two groups: those immediately centrifuged and those frozen 20–30 minutes before centrifugation. Data collection was carried out by examining serum cholesterol levels using an Erba Mannheim Chem-7 photometer. The results showed that the average cholesterol level in frozen samples was higher (161.4 mg/dL) compared to samples immediately centrifuged (140.45 mg/dL). The Mann-Whitney statistical test yielded a p-value of 0.006 (p<0.05), indicating a significant difference between the two treatments. This confirms that pre-analytical handling of blood specimens significantly impacts the validity of cholesterol test results. Therefore, careful attention to the pre-analytical stage is essential to ensure the accuracy of laboratory results.